Mapping Archaeological Site of Keraton Pleret Using Aerial Photograph - Warsini Handayani; Bagus Arif Setiawan; Bayu Argadyanto Prabawa; Taufik Hery Purwanto; Fredi Satya Candra Rosaji; Hendy Fatchurohman (Politeknik Negeri Batam, 2020)
As a cultural heritage, Site of Keraton (Palace) Pleret becomes an essential relic in Javanese history and culture to preserve and deliver ancient information for the next generation sustainably. On the other hand, this preservation is dealing with quite rapid built-up area development. Mapping can be a significant effort as primary data in cultural preservation management. This study aims to make a detailed site map of the Keraton Pleret and identify the existing land use in each site component. Through remote sensing data interpretation and analysis, identification and mapping of archaeological sites done by matching previous archaeological documents, field conditions, digital orthophoto from aerial photography, and digital topographic data (digital surface models, DSM). Site components were identified firstly by matching the existence of the street network and river from a topographic map with orthophoto to obtain site orientation based on artificial infrastructure and existing natural features. It was followed by matching between Keraton Pleret blueprint document, previous archaeological information, and orthophoto to identify and locate each site component. Existing land use information obtained by orthophoto interpretation. Data analysis shows the compatibility between spatial data used in this research and previous documents to identify components and result in Keraton Pleret site map. At present, most of the Keraton Pleret site area has been converted to buildings and paddy fields, strengthen the need for archaeological sites management which alongside community activities.